Inoculum Selection and Micro-Aeration for Biogas Production in Two-Stage Anaerobic Digestion of Palm Oil Mill Effluent (POME) (Jurnal Bahan Alam Terbarukan, 2019)
Two-stage anaerobic fluidized bed is an innovation in anaerobic digestion technology intended to handle liquid waste with high organic loading and complex substrate. The process is based on separation between acidogenic/acetogenic and methanogenic processes. The first stage is anaerobic process to convert substrate (represented as soluble chemical oxygen demand/sCOD) into volatile fatty acids (VFA). The second stage is methanogenic process to convert VFA into biogas. This study aimed to separate acidogenic/acetogenic and methanogenic processes by means of limited injection of air (micro-aeration) and inoculum selection. Micro-aeration was introduced in acidogenic/acetogenic stage because the relevant microbes were facultative so that the obligate anaerobic methanogens will be suppressed. On the other hand, the methanogenic reactor was kept completely anaerobic to ensure methanogenic dominance over acidogenic/acetogenic ones. Two sources of inoculums were used in this study, i.e. anaerobically digested biodiesel waste and anaerobically digested cow manure. Both inoculums were taken from active biogas reactor treating biodiesel waste and cow manure, respectively. Experiments were run in batch reactors treating palm oil mill effluent (POME) as the substrate for the acidogenic/acetogenic reactor. After the reaction in the first stage reached the minimum substrate concentration, the content of the reactor was used as the substrate for the methanogenic reactor as the second stage. Routine measurements were taken for sCOD and VFA concentrations, biogas production, and methane concentration in the biogas. Results confirmed that micro-aeration maintained good performance of acidogenic/acetogenic process, which was indicated by peaks in VFA accumulation, while suppressing methanogenic activities as no methane produced in this stage. Digested biodiesel waste was superior inoculum to be compared to digested cow manure with respect to sCOD removal. In the methanogenic stage, digested biodiesel waste also performed better as inoculum as it led to higher VFA conversion, higher biogas production rate, and higher methane content in the biogas.Â